COMPARISON OF BANKRUPTCY PREDICTION MODELS ANALYSIS (ALTMAN, SPRINGATE, GROVER, OHLSON AND ZMIJEWSKI) ON PT. ASURANSI HARTA AMAN PRATAMA, TBK. - Dyah Puspitasari Sunaryo Putri (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
PT. Asuransi Harta Aman Pratama, Tbk. is a financial services company which is specialized in general insurance. This research is conducted based on five annual reports spanned from 2012 to 2016 which are independently audited. This study, therefore, aims to compare with five models bankruptcy predictions; the Altman, Springate, Grover, Ohlson and Zmijewski. This study uses a quantitative research approach, using the financial statements data of PT. Asuransi Harta Aman Pratama, Tbk. which also has been published in BEI. This paper analyze the prediction of every method using analysis of variance. The result of this analysis show the differences between the applied models.